2000
DOI: 10.1046/j.1471-4159.2000.0741489.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of T‐Cadherin (CDH13, H‐Cadherin) in Human Brain and Its Characteristics as a Negative Growth Regulator of Epidermal Growth Factor in Neuroblastoma Cells

Abstract: Abstract:In the present study, we first examined the expression of T-cadherin in human CNS by northern blot analysis, immunohistochemical staining, and in situ hybridization. Northern blot analysis demonstrated expression of T-cadherin in human adult cerebral cortex, medulla, thalamus, and midbrain. Immunohistochemical staining with a newly generated monoclonal antibody, designated MA-511, revealed strong expression of Tcadherin in neural cell surface membrane and neurites in adult cerebral cortex, medulla obl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
154
2
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(160 citation statements)
references
References 16 publications
3
154
2
1
Order By: Relevance
“…31 A variety of studies have demonstrated the functional role of CDH13 in cell proliferation, the cell cycle, and epigenetic silencing in cancer, and CDH13 is now recognized as a tumor suppressor gene. CDH13 is believed to suppress the development of neural cells 31 and induce G2 (premiotic phase) arrest in astrocytomas via p21.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 A variety of studies have demonstrated the functional role of CDH13 in cell proliferation, the cell cycle, and epigenetic silencing in cancer, and CDH13 is now recognized as a tumor suppressor gene. CDH13 is believed to suppress the development of neural cells 31 and induce G2 (premiotic phase) arrest in astrocytomas via p21.…”
Section: Discussionmentioning
confidence: 99%
“…Among those that fulfilled both of these criteria, we chose 251 probes that showed remarkably high expression only in fluorescentnegative tumors (median intensity of expression signal > 1.0). We then selected 68 cancer-related genes (80 probes) as functionally annotated by the Ingenuity Pathways Analysis Knowledge Base, and finally pinpointed CDH13, known as a tumor suppressor gene, 31 as the most likely determinant of a 5-ALA-induced fluorescence signal in glioma. In general, a tumor suppressor gene is related to the malignancy of a tumor, which is believed to be corre-lated with a positive rate of 5-ALA-induced fluorescence signal.…”
Section: Selection Of Genes Related To 5-ala-induced Tumor Fluorescenmentioning
confidence: 99%
“…A second possibility is that APN might have other signal transduction pathways in addition to AdipoR1 and ‐R2. For instance, it will be interesting to determine if T‐cadherin, which is abundantly expressed in brain52 and is known to bind APN,53 might affect expression of APN.…”
Section: Apn May Promote Neurodegeneration In Ad Through Novel Mechanmentioning
confidence: 99%
“…This cellular proliferation is blocked by virusmediated adiponectin expression (34). Interestingly, T-cadherin can regulate growth of cells in the nervous system (35). Tcadherin suppressed the growth of astrocytes and was reduced in a glioblastoma cell line (36), and reexpression of T-cadherin in this cell line induced growth arrest, which depended on p21 (CIP1͞WAF1) expression.…”
Section: Divalent Cations Are Required For Adiponectin Binding To T-cmentioning
confidence: 99%